2016
DOI: 10.1530/joe-15-0530
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen deprivation in primate pregnancy leads to insulin resistance in offspring

Abstract: This study tested the hypothesis that estrogen programs mechanisms within the primate fetus that promote insulin sensitivity and glucose homeostasis in offspring. Glucose tolerance tests were performed longitudinally in prepubertal offspring of baboons untreated or treated on days 100 to 165/175 of gestation (term is 184 days) with the aromatase inhibitor letrozole which decreased fetal estradiol levels by 95%. Basal plasma insulin levels were over 2-fold greater in offspring delivered to letrozole-treated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 90 publications
10
35
0
1
Order By: Relevance
“…An iv glucose tolerance test was performed essentially as described previously [1], according to the established method of Overkamp et al [18], sequentially (1–4 times) on each baboon offspring at 6–12 month intervals after onset of puberty between the ages of 4¼ (females)/5 (males) years and 8 years of age. Intravenous glucose tolerance test results in individual animals did not change between 4¼–8 years of age and thus the data obtained from the individual iv GTT performed was averaged to yield a single value for each animal.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…An iv glucose tolerance test was performed essentially as described previously [1], according to the established method of Overkamp et al [18], sequentially (1–4 times) on each baboon offspring at 6–12 month intervals after onset of puberty between the ages of 4¼ (females)/5 (males) years and 8 years of age. Intravenous glucose tolerance test results in individual animals did not change between 4¼–8 years of age and thus the data obtained from the individual iv GTT performed was averaged to yield a single value for each animal.…”
Section: Methodsmentioning
confidence: 99%
“…basal fasting), 1, 3, 5, 10, 20, 40, 60 and 90 min before/after dextrose administration. Blood glucose levels were determined via an iStat Portable Clinical Analyzer (Model #210003, Abbott Labs, East Windsor, NJ) on 0.1 ml of blood and insulin determined in stored (−20 °C) plasma samples using a solid-phase chemiluminescent immunometric assay via an Immulite System (Siemens Healthcare Diagnostics, Tarrytown, NY) as described previously [1]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin resistance is implied by the high blood glucose in Gnrhr null pups; this suggests that a decrease in intracellular glucose and fat accumulation would occur in adipose tissue. It has been shown that estrogen deprivation in pregnancy leads to insulin resistance in a primate offspring; this may explain the phenomenon in the Gnrhr pups who are are born at an early stage of development and lack maternal or endogenous estradiol thereafter [64]. This could help to explain the connection between loss of estradiol and implied insulin resistance in young pups.…”
Section: Discussionmentioning
confidence: 99%